Alternative intrapopulation life-history strategies and their trade-offs in an African annual fish - Polačik, M; Blažek, R; Režucha, R; Vrtílek, M; Terzibasi Tozzini, E; Reichard, M (Journal of evolutionary biology, 2014)
In ephemeral habitats, the same genotypes cope with unpredictable environmental conditions, favouring the evolution of developmental plasticity and alternative life-history strategies (ALHS). We tested the existence of intrapopulation ALHS in an annual killifish, Nothobranchius furzeri, inhabiting temporary pools. The pools are either primary (persisting throughout the whole rainy season) or secondary (refilled after desiccation of the initial pool), representing alternative niches. The unpredictable conditions led to the evolution of reproductive bet-hedging with asynchronous embryonic development. We used a common garden experiment to test whether the duration of embryonic period is associated with post-embryonic life-history traits. Fish with rapid embryonic development (secondary pool strategy, high risk of desiccation) produced phenotypes with more rapid life-history traits than fish with slow embryonic development (primary pool strategy). The fast fish were smaller at hatching but had larger yolk sac reserves. Their post-hatching growth was more rapid, and they matured earlier. Further, fast fish grew to a smaller body size and died earlier than slow fish. No differences in fecundity, propensity to mate or physiological ageing were found, demonstrating a combination of plastic responses and constraints. Such developmentally related within-population plasticity in life history is exceptional among vertebrates.
Keywords: Afrika; Body Size; polyphenism; Fundulidae; analýza přežití; Ponds; ekosystém; fertilita; Survival Analysis; velikost těla; mužské pohlaví; fenotyp; rybníky; Phenotype; senescence rate; Africa; ženské pohlaví; zvířata; Fertility; periodic habitat; alternative embryonic pathway; lifespan; Female; Ecosystem; phenotypic plasticity; Male; Animals